2011
DOI: 10.1186/1746-6148-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Marek's Disease Virus (MDV) infection: parameter estimates for mortality rate and infectiousness

Abstract: BackgroundMarek's disease virus (MDV) is an economically important oncogenic herpesvirus of poultry. Since the 1960s, increasingly virulent strains have caused continued poultry industry production losses worldwide. To understand the mechanisms of this virulence evolution and to evaluate the epidemiological consequences of putative control strategies, it is imperative to understand how virulence is defined and how this correlates with host mortality and infectiousness during MDV infection. We present a mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 31 publications
0
42
0
2
Order By: Relevance
“…Several of our model parameters are already known from previous experiments. These include the rate of dust production as a function of bird age d ( τ ) (Atkins et al, 2013a), the incubation period of the virus (Islam and Walkden-Brown, 2007; Read et al, 2015), which is determined by β , and the mean transmission rate of the virus μ α (Atkins et al, 2011, 2013b). Placement dates, load out dates, and flock sizes were fixed at known values from the respective datasets being modeled.…”
Section: Methodsmentioning
confidence: 99%
“…Several of our model parameters are already known from previous experiments. These include the rate of dust production as a function of bird age d ( τ ) (Atkins et al, 2013a), the incubation period of the virus (Islam and Walkden-Brown, 2007; Read et al, 2015), which is determined by β , and the mean transmission rate of the virus μ α (Atkins et al, 2011, 2013b). Placement dates, load out dates, and flock sizes were fixed at known values from the respective datasets being modeled.…”
Section: Methodsmentioning
confidence: 99%
“…We assume that there is a positive relationship between the transmission rate ðβÞ of the parasite and the extent of damage caused to the host, resulting in a loss of fecundity for infected individuals. Such relationships are typically used to study the evolution of virulence in lethal infections (29)(30)(31), and are supported by strong evidence from a number of systems (32,33). Few studies have directly looked for transmission-virulence relationships among parasites that reduce host fecundity rather than increase mortality, although Ebert et al (34) found a negative relationship between reproduction by a bacterial parasite (Pasteuria ramosa) and the fecundity of its host (Daphnia magna).…”
Section: Significancementioning
confidence: 99%
“…Estas lesiones están influenciadas por la presencia de infiltrado linfocitario lo que ha demostrado que a medida que la cepa se hace más virulenta el infiltrado linfocitario es mayor lo que puede conducir a la atrofia del timo y la bursa; esta característica ha servido para prever que todas estas cepas han tenido una evolución continua en el tiempo para cambiar su virulencia 30,50,54,61 , lo que sugiere que los tres serotipos pueden desarrollar rápidamente características biológicas y moleculares alteradas, indicando que pueden existir mutaciones espontáneas en su genoma 15,16,17 .…”
Section: Virus De La Enfermedad De Marek Y Clasificación Patotípicaunclassified
“…El virus de la Enfermedad de Marek (VEM) es uno de los agentes infecciosos aviares con mayor impacto en la producción de pollo de engorde y gallina ponedora, la Enfermedad de Marek (EM) es causada por este agente y tiene gran importancia en muchos países ya que se pueden presentar decomisos y mortalidad que afectan la economía de la industria avícola 30 Las características genéticas y moleculares del VEM han sido evaluadas y documentadas a través publicaciones científicas, las cuales reportan en consenso la diversidad genética que poseen cada uno de los serotipos del virus, las características genéticas hacen que este virus tenga singulares estrategias en su replicación, las cuales afectan considerablemente la respuesta inmune del ave a la infección y la efectividad en controlar su infección y diseminación debido principalmente a la producción de interferones que actúan directamente sobre la respuesta inmune innata contra el virus 29,30 . Esto permite que el virus evolucione en el tiempo evitando su exposición al sistema inmune, impidiendo su eliminación del hospedero e incrementado su patogénesis 46,50 .…”
Section: Introductionunclassified